Analysis of the Influence of Roundness of Probe on the Accuracy of Gear Polar Coordinate Measuring Method - Yubin Teng; Tao Sun (Jixie chuandong)
When the polar coordinate method is used to measure the involute tooth profile deviation of cylindrical gear，the contact point between the spherical probe and the tooth profile changes constantly on the spherical surface of the probe. The roundness error of the ball probe will affect the measurement accuracy. In order to solve this problem，an ellipse ball probe is used to simulate the roundness error of the ball probe，and a calculation method is proposed to calculate the measurement error produced by the ellipsoid probe itself. This method is used to calculate and analyze the measurement errors of different types of probes when measuring gears of different specifications. The size and variation rules of the measurement errors of elliptical ball probes under various conditions are summarized.